The role of ion channels in the hypoxia-induced aggressiveness of glioblastoma - Sforna, Luigi; Cenciarini, Marta; Belia, Silvia; D’Adamo, Maria Cristina; Pessia, Mauro; Franciolini, Fabio; Catacuzzeno, Luigi (Frontiers in Cellular Neuroscience, 2015)
The malignancy of glioblastoma multiform (GBM), the most common and aggressive form of human brain tumors, strongly correlates with the presence of hypoxic areas, but the mechanisms controlling the hypoxia-induced aggressiveness are still unclear. GBM cells express a number of ion channels whose activity supports cell volume changes and increases in the cytosolic Ca2+ concentration, ultimately leading to cell proliferation, migration or death. In several cell types it has previously been shown that low oxygen levels regulate the expression and activity of these channels, and more recent data indicate that this also occurs in GBM cells. Based on these findings, it may be hypothesized that the modulation of ion channel activity or expression by the hypoxic environment may participate to the acquisition of the aggressive phenotype observed in GBM cells residing in a hypoxic environment. If this hypothesis will be confirmed, the use of available ion channels modulators may be considered for implementing novel therapeutic strategies against these tumors.